REKONSILIASI PERGERAKAN MAHASISWA ISLAM (PMII) MENJADI BADAN OTONOM NAHDLATUL ULAMA (NU): (KOMUNIKASI ORGANISASI DALAM PENYELESAIAN KONFLIK) - Novri, Novriana Dewi (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
In 1972 the Islamic Student Movement of Indonesia (PMII) decided to dissociate itself and declared out of the autonomous body Nahdlatul Ulama (NU). The conflict got worse when in the 2015 NU Congress in Jombang declared withdrawal of PMII back into autonomous body of NU or in this research called reconciliation. But the decision has not received legal reciprocity from the PMII. This study aims to analyze internal organizational communications conducted by the NU's Executive Board against PMII so that the PMII is structurally a truly part of the NU. The paradigm used in this research is constructivism with case study research method. Data collection is done through two ways: interview and documentation. From the results of research and discussion, it can be concluded that the reconciliation made by PBNU to bring PMII back into autonomous body of NU has not yet been successful. Internal communication by PBNU and PMII in this case is vertical communication - tends to be downward communication (from superiors to subordinates), which gives little room towards PMII. Furthermore, the dissemination of information / messages is done by a sequential method of 'who speaks to whom' pattern through people who have a central position. This method utilizes the leadership of each level of the PMII organizational structure to convey messages conveyed by PBNU to each member of the structure below.